Dictated by the Screen: Digital Payment Technoculture and the Normalization of a Cashless Lifestyle among University Students - Asti Hanafi; Fredy Hermanto (Journal of General Education and Humanities, 2026)
This research examines how digital payment technology functions as a technocultural practice normalizing a cashless lifestyle among university students at Semarang State University. This study employed a qualitative descriptive approach using field observation and semi-structured in-depth interviews with 20 purposively selected student participants who regularly use digital payment systems. Thematic analysis guided by Pierre Bourdieu's social practice framework organized data into three analytical dimensions: habitus, capital, and arena. Findings demonstrate that digital payment adoption has transformed from conscious technological accommodation into a reflexive behavioral practice deeply internalized within campus life. Students exhibit diminished spending awareness, increased technological dependence, and reoriented monetary perception from tangible objects to digital representations. The research introduces the analytical concept "Screen Dictates" to illuminate how payment technology interfaces actively regulate consumption patterns through subliminal mechanisms. Conclusions emphasize that cashless payment systems function not as neutral economic innovations but as technocultural constructions fundamentally reshaping young adults' economic subjectivity and consumption practices.